2009
DOI: 10.1099/vir.0.008870-0
|View full text |Cite
|
Sign up to set email alerts
|

Infectious bursal disease virus persistently infects bursal B-lymphoid DT40 cells

Abstract: Infectious bursal disease virus (IBDV), an important avian pathogen, exhibits a specific tropism for immature B-lymphocyte populations. We have investigated the ability of IBDV to replicate in chicken B-lymphoid DT40 cells, a tumour cell line derived from the bursa of Fabricius of a chicken infected with avian leukosis virus. Our results show that IBDV persistently infects DT40 cells. Establishment of the persistent infection is associated with an extensive remodelling of the hypervariable region of the VP2 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…The molecular analyses using RT-PCR, sequence, and sequence analysis revealed that the two isolates are phylogenetically related to the vvIBDV found in Asia, Europe, Middle East, and Africa due to the presence of A222 [ 51 , 52 ] and I242, I256, I294, and S299 [ 51 ] in their VP2 hypervariable amino acid composition compared to the caIBDV or vaIBDV that possessed V222, VA, or E256 or the serotype 2 viruses that possessed P222, V242, I or S256, N or F294 and T or P299 [ 51 ] in the same region. The presence of the 233–236 IDA motif in our strains just like other IBDV indicates that these viruses could adapt to cell culture because these amino acids were reported to be important for cell culture adaptation [ 51 , 53 ] via the integrin receptors. Furthermore, during the CEE passaging, UPM190 isolate acquired a mutation at D279N at EP12, a mutation that was reported to be part of the two changes observed in attenuated and/or cell culture adapted IBD viruses [ 7 , 54 56 ].…”
Section: Discussionmentioning
confidence: 83%
“…The molecular analyses using RT-PCR, sequence, and sequence analysis revealed that the two isolates are phylogenetically related to the vvIBDV found in Asia, Europe, Middle East, and Africa due to the presence of A222 [ 51 , 52 ] and I242, I256, I294, and S299 [ 51 ] in their VP2 hypervariable amino acid composition compared to the caIBDV or vaIBDV that possessed V222, VA, or E256 or the serotype 2 viruses that possessed P222, V242, I or S256, N or F294 and T or P299 [ 51 ] in the same region. The presence of the 233–236 IDA motif in our strains just like other IBDV indicates that these viruses could adapt to cell culture because these amino acids were reported to be important for cell culture adaptation [ 51 , 53 ] via the integrin receptors. Furthermore, during the CEE passaging, UPM190 isolate acquired a mutation at D279N at EP12, a mutation that was reported to be part of the two changes observed in attenuated and/or cell culture adapted IBD viruses [ 7 , 54 56 ].…”
Section: Discussionmentioning
confidence: 83%
“…We next sought to decipher the functional role of VP3 association with endosomal membranes in the context of the viral replication cycle. Noticeably, our first idea was to profit from the reverse genetic approach developed in the laboratory of J. F. Rodríguez and previously described (57) to generate P2-mutated viral progeny. To this end, a plasmid harboring a mutant version of segment A cDNA containing the P2 substitutions was constructed, but unfortunately, mutated viral progeny was not generated.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of neutralizing antibody in the blood did not prevent virus delivery to the tissues. In the present study, we did not explore the means of virus delivery to tissues, although it is possible that IBDV is picked up by gut macrophages or other lymphoid cells and then dispersed throughout the body .…”
Section: Discussionmentioning
confidence: 99%